“The Knight in the Panther’s Skin” by Shota Rustaveli: Salutogenic Aspects - Shengelia, Ramaz; Jojua, Levan (DELTOS, 2024)
The article provides a discussion of the specific salutogenic aspects of medical knowledge in Shota Rustaveli’s “The Knight in the Panther’s Skin” – a distinguished piece of Georgian literature. Consideration of specific passages from the poem and corresponding commentary demonstrates the author’s medical knowledge, as he stresses the significance of positive emotions, a healthy environment, and mood on human health, thus having a therapeutic effect.. Regarding the knowledge reflected in similar scientific literature, which is significant for the history of Georgian medicine, the work offers a more specific and, in some cases, newer vision of the salutogenic aspects in “The Knight in the Panther’s Skin”. Along with the author’s knowledge, we emphasise the fact that during that period, there was a logical link between the medical-biological thinking of the era known as the “Golden Age”. This connection represents a natural expression of the level of the scientific sphere, simultaneously with cultural and political progress in the country. In addition to providing an overview of specific medical areas in “The Knight in the Panther’s Skin”, the article will explore the scientific and other literature of the era and a later period, where similar approaches are described. The issues discussed in the article, regarding their nature and different aspects, could be of interest for studying the history of medicine of that specific era.